Interaction of food packaging material and selected food components under high pressure - Ludwig, Horst; Marx, Heidger; Tauscher, Bernhard (High pressure research, 1994)
Interactions between ethanolic solutions of p-cymene and acetophenone and different polymer packaging materials. were studied at 500 MPa and 25° C. p-Cymene solution, filled into low-density polyethylene bags, lost 30% of its aroma concentration after 24 h at 500 MPa compared to a 60% loss at atmospheric pressure. The decrease was strongest within the first 15 min. Using LDPE/HDPE/LDPE bags, losses were 20% and 30%, resp. Applying the “bag in the bag” method, p-cymene concentrations measured inside and outside the inner bag has shown sorption by the pressurized film to be one third of that by the non-pressurized. In PET/AI/LDPE bags impermeable to p-cymene, sorption was confined to the inner LDPE layer and caused higher loss in the non-pressurized sample. Acetophenone has not been found to interact with the polymer during pressure treatment, while at atmospheric pressure sorption loss in aroma concentration was nearly 70% after 60 h.
Online veröffentlicht: 19. August 2006
Gesehen am 14.01.2026